The Influence of Non-governmental organizations on the environmental law- consequences on the international legal personality of the state - Gordanic, Jelica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Non-governmental organizations have achieved significant success in the development of international environmental law during the last decades. Their activities such as lobbying, attracting public attention and media campaigns have contributed the development of certain environmental issues. International and regional agreements provide various forms of participation and cooperation with NGOs. The author considers whether the growing influence of NGOs in the development of environmental law has consequences for the state as a subject of international law. Through their activities, NGOs had acquired certain elements of international legal personality and had entered the domain which traditionally belongs to the state. This phenomenon raises the question of the potential transformation of the concept of the international legal personality, as well as the readiness of international law for flexibility regarding this issue. The author concludes that, despite the growing importance of NGOs in the development of environmental law, the concept of international law is not ready for transformation. In overcoming this problem, states should make the best by using the role and existence of NGOs, and, in the area of environmental law, with joint efforts, continue the development of this branch of law.